"World-beating" Pandemic Responses: Ironical, Sarcastic, and Satirical Use of War and Competition Metaphors in the Context of COVID-19 Pandemic. (3rd April 2022) - Musolff, Andreas
ABSTRACT: The COVID-19 pandemic tempted some governments to promise to wage "war" against it and implement "world-beating" control mechanisms. In view of their limited success, such claims soon came in for massive criticism, which turned their hyperbolic implicatures and figurative framing against them. Our paper focuses on such cases of "metaphor reversal" within the context of the British public debate. Drawing on examples from a corpus of media texts, we identify several types of the dissociation, including irony (i.e., putting the figurative claims' implicatures in doubt implicitly), sarcasm (i.e., explicitly decrying their plausibility) and satire (i.e., exhibiting their presumed absurdity), with reference to theory models of irony (echo, pretense, mental space structuring). In conclusion, we argue that the seesaw of exchanges between exaggerated figurative claims of (imminent) success made by government politicians and their sarcastic-satirical debunking by media and opposition politicians has an ambivalent effect on public discourse. On the one hand, it highlights contrasts in policy and policy assessment and may also have entertainment value, but on the other hand, it conveys experiences of repeated, serial exposure of hyperbolic government rhetoric. This in turn may lead to an erosion of trust in official communication as being unrealistic, which may foster beliefs in conspiracy theories.